Pengaruh Model Pembelajaran Inquiry Berbantuan Media Flash Card terhadap Kompetensi Pengetahuan IPAS Siswa IV SD - Ni Nyoman Christina Srimaharani; I Gusti Agung Ayu Wulandari; D.B.Kt. Ngr. Semara Putra (Journal on Education, 2023)
This study aims to determine the influence of the inquiry learning model with flash card media on the competence of IPAS knowledge of grade IV. This type of research is a pseudo-experimental study with a nonequivalent control group design. The population in this study was 91 grade IV. Samples taken with purposive sampling technique. The collection of IPAS knowledge competency data was carried out using the test method in the form of an ordinary multiple-choice objective test of 30 questions. The data obtained were analyzed using t-test analysis. The results of the data analysis were obtained t count = 6.357 > ttable = 2.021 for significance 5% and dk = 46, so Ho was rejected and Ha was accepted. There is a significant difference in IPAS knowledge competence between students who are taught the flash card media-assisted inquiry learning model and students who are taught by conventional learning. The average score of the IPAS knowledge competency score in the group taught with the inquiry learning model assisted by media flash card was 85.04, while in the group taught with conventional learning was 72.39. It can be concluded that the inquiry learning model assisted by flash card media affects the competence of IPAS knowledge of grade IV.